2018
DOI: 10.1101/379057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cytoplasmic GOLD Protein Controls Cell Polarity

Abstract: Phosphoinositide lipids provide spatial landmarks during polarized secretion.Here, we elucidate a role for phosphatidylinositol 4-phosphate (PI4P) metabolism in the control of cell polarity. In budding yeast, PI4P is enriched at the plasma membrane of growing daughter cells. Upon heat shock however, PI4P rapidly increases at the plasma membrane in mother cells resulting in a more uniform PI4P distribution. Rather than phosphoinositide kinase activation, PI4P hydrolysis is impaired to generate the heat-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Among many possibilities, they could correspond to ER-plasma membrane contact sites. Indeed, in yeast, Stt4 reside at these contacts (Omnus et al, 2018). Another hypothesis is that they could be a zone of attachment between the plasma membrane and the actin cytoskeleton.…”
Section: Formation and Possible Function Of Pi4kα1-containing Nanoclustersmentioning
confidence: 99%
“…Among many possibilities, they could correspond to ER-plasma membrane contact sites. Indeed, in yeast, Stt4 reside at these contacts (Omnus et al, 2018). Another hypothesis is that they could be a zone of attachment between the plasma membrane and the actin cytoskeleton.…”
Section: Formation and Possible Function Of Pi4kα1-containing Nanoclustersmentioning
confidence: 99%
“…Multiplex lipid binding domains can appear in homo‐tandems of PH domains such as in mammalian TAPP1 and TAPP2 (Li et al, 2013), as hetero‐tandems with other lipid binding domains such as the tandem PX‐PH domains in yeast Bem3p that cooperatively bind membrane lipids (Ali et al, 2018) or a combination of tandem PH domains and additional motifs such as for human ARAP3 (Craig et al, 2010). Tandem configurations of PH domains that appear naturally as single domains were artificially created for rat and human PH PLCδ1 (GFP‐2xPH PLCδ1 ) and tested in yeast (Fairn et al, 2011; Mioka et al, 2020; Omnus et al, 2018; Rodríguez‐Escudero et al, 2018; Thomas et al, 2022; Wild et al, 2004). In direct comparison to GFP‐PH PLCδ1 , GFP‐2xPH PLCδ1 showed that previously weak PM binding with high levels of cytosolic localization was shifted to strong PM targeting in yeast (Levine & Munro, 2002; Wild et al, 2004).…”
Section: Introductionmentioning
confidence: 99%